An Interactive Media-Based Model for Qur’anic Learning at Saengsattha Elementary School - Putri Agil (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze an interactive media-based model for Qur’anic learning at Saengsattha Elementary School. The research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving teachers and students as research participants. The findings reveal that the interactive media-based learning model is implemented through the use of various media, such as digital applications, instructional videos, and visual aids that support Qur’anic learning. This model enhances students’ learning interest, engagement, and understanding of Qur’anic recitation. In addition, teachers play a crucial role in managing and integrating interactive media into the learning process. However, several challenges were identified, including limited technological facilities and teachers’ competencies in operating interactive media. Therefore, training and institutional support are necessary to optimize the implementation of this learning model.